Extracellular matrix-cell interactions: Focus on therapeutic applications - A. Sainio; H. Jarvelainen (ELSEVIER SCIENCE INC, 2022)
Extracellular matrix (ECM) macromolecules together with a multitude of different molecules residing in the extracellular space play a vital role in the regulation of cellular phenotype and behavior. This is achieved via constant reciprocal interactions between the molecules of the ECM and the cells. The ECM-cell interactions are mediated via cell surface receptors either directly or indirectly with co-operative molecules. The ECM is also under perpetual remodeling process influencing cell-signaling pathways on its part. The fragmentation of ECM macromolecules provides even further complexity for the intricate environment of the cells. However, as long as the interactions between the ECM and the cells are in balance, the health of the body is retained. Alternatively, any dysregulation in these interactions can lead to pathological processes and finally to various diseases. Thus, therapeutic applications that are based on retaining normal ECM-cell interactions are highly rationale. Moreover, in the light of the current knowledge, also concurrent multi-targeting of the complex ECM-cell interactions is required for potent pharmacotherapies to be developed in the future.